(untitled) (International Journal of Environmental Sciences, 2025)
Skeletal muscle atrophy is a progressive condition characterized by loss of muscle mass, strength, and function due to enhanced proteolysis and impaired regeneration. Current pharmacologic interventions largely fail to provide dual-action benefits, leaving a critical gap in effective therapy. This study aimed to evaluate the preventive and regenerative potential of a novel compound, Curcumin-Boron Complex (Cur-B), in a dexamethasone-induced rat model of muscle atrophy. Twenty-four adult male Wistar rats were randomly divided into four groups: normal control, atrophy control, preventive treatment, and reversal treatment. Muscle atrophy was induced using intramuscular dexamethasone. Cur-B (10 mg/kg/day) was administered either concurrently (preventive) or after atrophy establishment (reversal). Efficacy was assessed using histopathology (H&E, Masson’s Trichrome), immunohistochemistry (Atrogin-1, MuRF1, Pax7, MyoD, Myogenin), qRT-PCR, Western blotting, and ELISA. Cur-B significantly restored muscle weight in both preventive (1.66 ± 0.10 g) and reversal (1.57 ± 0.09 g) groups versus atrophy control (1.20 ± 0.08 g). Histological analysis showed increased muscle fiber cross-sectional area and reduced fibrosis. Cur-B downregulated catabolic markers (Atrogin-1: 85.2% to 41.5%) and upregulated regenerative markers (Pax7: 4.2 to 9.1 cells/field). Biochemical assays revealed reductions in IL-6 and MDA, and restoration of antioxidant enzymes. Cur-B exhibits significant dual-action efficacy in preventing and reversing muscle atrophy through anti-catabolic, anti-inflammatory, and pro-regenerative mechanisms. These results provide compelling translational evidence for Cur-B as a candidate therapeutic agent for muscle-wasting disorders.